Diagnostic and prognostic role of platelets in patients with sepsis and septic shock - Schupp, Tobias; Weidner, Kathrin; Rusnak, Jonas; Jawhar, Schanas; Forner, Jan; Dulatahu, Floriana; Brück, Lea Marie; Hoffmann, Ursula; Kittel, Maximilian; Bertsch, Thomas; Akın, Ibrahim; Behnes, Michael (Platelets, 2023)
Studies investigating the prognostic role of platelets commonly include critically ill patients, whereas data regarding the prognostic impact of platelet count in patients admitted with sepsis and septic shock is limited. Therefore, the study investigates the prognostic role of platelet count in patients with sepsis and septic shock. Consecutive patients with sepsis and septic shock from 2019 to 2021 were included monocentrically. Blood samples were retrieved from the day of disease onset (day 1), days 2, 3, 5, 7 and 10. Firstly, the diagnostic value of platelet count was tested for septic shock compared to sepsis. Secondly, the prognostic value of platelet count was tested for 30-day all-cause mortality. Statistical analyses included univariable t-test, Spearman’s correlation, C-statistics, Kaplan-Meier analyses, as well as multivariable mixed analysis of variance (ANOVA), Cox proportional regression analyses and propensity score matching. A total of 358 patients with sepsis and septic shock were included with a median platelet count of 176 × 106/ml. The presence of thrombocytopenia (i.e. <150 × 106/ml) was associated with increased risk of 30-day mortality (HR = 1.409; 95% CI 1.057-1.878; p = .019), which was still demonstrated after propensity score matching. During the course of sepsis, a nadir was observed on sepsis day 5 with a decrease in the mean platelet count by 21.5%. Especially serum lactate, mean arterial pressure and the presence of malignancies were found to predict platelet decline during the course of sepsis/septic shock. The presence of platelet decline >25% was associated with an increased risk of 30-day all-cause mortality (HR = 1.484; 95% CI 1.045-2.109; p = .028). Following platelet decline, recovery was observed from day 5 to day 10 (mean increase 7.5%). However, platelet recovery was not found to be associated with 30-day all-cause mortality (HR = 1.072; 95% CI 0.567-2.026; p = .832). In conclusion, both thrombocytopenia and platelet decline during the course of sepsis were associated with an increased risk of 30-day all-mortality in patients admitted with sepsis or septic shock.
Published online: 09 Dec 2022
Gesehen am 06.02.2023